Jako pierwszą pozdrawiam Gdynię... ([S.l. : s.n.], 2005)
Plakat Jan Paweł II na tle portu gdyńskiego.
Keywords: Jan Paweł -- II -- (papież ; -- 1920-2005) -- podróże -- Polska -- Gdynia; Gdynia (Polska) -- 1970-2000 -- plakaty